Enabling High Loading in Single‐Atom Catalysts on Bare Substrate with Chemical Scissors by Saturating the Anchoring Sites (Small 19/2022). Issue 19 (12th May 2022) - Li, Ang; Kan, Erjun; Chen, Shuangming; Du, Zhengwei; Liu, Xuan; Wang, Tongyu; Zhu, Wenjin; Huo, Hailing; Ma, Jingjing; Liu, Dong; Song, Li; Feng, Hao; et al.
Abstract : Single‐Atom Catalysts The low loading of single‐atom catalysts makes it difficult to improve their overall activity. In article number 2200073, Ang Li, Erjun Kan, Li Song, Jinlong Gong, and co‐workers report a chemical scissors strategy to saturate the anchoring sites for single atoms, which elevates the loading of Pd single atoms even on bare substrate with only a few anchoring sites.